The 2021 Veblen-Commons Award Recipient: Deborah M. Figart: Good Work. Issue 2 (3rd April 2021) - Figart, Deborah M.
Abstract : COVID-19 has exposed underlying weaknesses in the economy, including the political economic institutions structuring work. The labor market has moved toward more precarious work, negatively affecting job quality and well-being. After a summary of the current context shaping work, I discuss a new, 2021 Top Ten list of policy proposals aimed at institutionalizing good work. This list revises ten public policies I proposed in 2003, and reconsiders how they might be updated given evolving economic structures and context. Theoretically, the article draws upon major concepts in institutional and heterodox economics: progressive institutional change, invidious distinctions, countervailing power, social balance, capabilities, caring labor, and social provisioning.